Correction possibilities of drug-induced liver toxicity in the treatment of patients with blood system tumors - V. B. Larionova; A. V. Snegovoy (Онкогематология)
Background. In modern oncohematology achieved notable success due to the intensification and development of new chemotherapy regimens. However, the side effects of anticancer drugs, due to low selectivity of most of them, are a serious limitation to achieve their maximal therapeutic effect. Although doctors are aware of the possibility of hepatotoxic reactions to various drugs, in clinical practice, the diagnosis of drug-induced liver injury is formulated unreasonably rarely. This speculation is due to several factors: in some cases, the latent course of drug-induced liver injury, often inadequate interpretation of clinical symptoms and laboratory parameters, and sometimes insufficiently thorough collection of anamnesis. A particularly difficult problem for a doctor is the development of drug-induced hepatotoxicity in patients for whom the “causal” drug is prescribed for vital indications, in particular, polychemotherapy in cancer patients, complex antimicrobial therapy and antiviral therapy for febrile neutropenia or sepsis, etc. In these situations, on the one hand, treatment cancellation is impossible due to the risk of disease progression, on the other hand, its continuation is undesirable due to the risk of severe hepatitis. In addition, multicomponent therapy, which is a complex of potentially hepatotoxic substances, often does not allow specifying the substance that caused the pathological reaction. At the same time, it is obvious that the hepatocyte, the main cell of the hepatic parenchyma, remains the center of the organ pathology. The variety of biochemical processes occurring with ademetionine participation served as the basis for conducting clinical studies in order to correct drug-induced liver toxicity in the treatment of patients with blood system tumors.The objective of the study is to assess laboratory and clinical parameters of drug-induced liver injury (DILI), intrahepatic cholestasis in the study of homeostasis disorders in patients with hematological malignancies and chemotherapy-induced hepatotoxicity.Materials and methods. The study involved 45 patients with blood system tumors, who had chemotherapy-induced hepatocellular failure. To describe the population of DILI patients, we collected demographic data, clarified the underlying liver disease in each patient, and analyzed the diagnostic criteria for chronic liver disease due to DILI. Clinical signs and symptoms of cholestasis (jaundice, pruritus, weakness), as well as manifestations of a depressive state and asthenic syndrome – mood (mild, moderate and severe), normalization of sleep rhythm, memory improvement, general health were assessed. Changes in laboratory parameters of liver function were studied. In 20 patients with blood system tumors, the biochemical parameters associated with cell metabolism were analyzed – lipid peroxidation, nitric oxide (NOx ) level, impaired liver detoxification capacity by glutathione level and glutathione-S-transferase activity. The treatment regimens for drug-induced hepatotoxicity included the Heptral, which was prescribed until stable normalization of liver function.Results. All patients with developed liver failure showed metabolic disorders. The use of ademetionine has shown significant effect. The NO and superoxide dismutase in most patients decreased significantly and almost corresponded to the norm. Normalization of the glutathione system parameters was also observed. One of the mechanisms of Heptral protective effect is an increase in the glutathione synthesis. The improvement in laboratory parameters was accompanied by the disappearance of DILI and intrahepatic cholestasis symptoms. This is confirmed by significant statistical correlations between them and indicates the ademetionine efficacy to recovery of hepatocytes function. When using ademetionine, the most pronounced reduction among biochemical parameters was observed in alkaline phosphatase and γ-glutamyl transpeptidase, markers of cholestasis syndrome. In addition, serum bilirubin concentration and alanine and aspartic transaminases activity (albeit to a lesser extent) decreased significantly. Clinical and biochemical effects, as a rule, persisted for several months after completion of therapy. Decrease in biochemical parameters characterizing cholestasis and cytolysis (positive dynamics of alanine and aspartic transaminases, alkaline phosphatase, γ-glutamyl transpeptidase, bilirubin) was accompanied by an improvement and normalization of patients’ well-being. When assessing the depression and asthenic syndrome, it was noted that the duration of Heptral therapy is important.Conclusion. The results obtained were the basis for the development of supportive therapy programs to prevent and reduce liver toxicity during chemotherapy. Rational approaches to the liver metabolic disorders correction – a real way to increase the treatment efficacy and improve the quality of life of patients with blood system tumors.